Designing a Zn–Ag Catalyst Matrix and Electrolyzer System for CO2 Conversion to CO and Beyond. Issue 1 (21st October 2021) - Lamaison, Sarah; Wakerley, David; Kracke, Frauke; Moore, Thomas; Zhou, Lan; Lee, Dong Un; Wang, Lei; Hubert, McKenzie A.; Aviles Acosta, Jaime E.; Gregoire, John M.; Duoss, Eric B.; Baker, Sarah; et al.
Abstract: CO2 emissions can be transformed into high‐added‐value commodities through CO2 electrocatalysis; however, efficient low‐cost electrocatalysts are needed for global scale‐up. Inspired by other emerging technologies, the authors report the development of a gas diffusion electrode containing highly dispersed Ag sites in a low‐cost Zn matrix. This catalyst shows unprecedented Ag mass activity for CO production: − 614 mA cm −2 at 0.17 mg of Ag. Subsequent electrolyte engineering demonstrates that halide anions can further improve stability and activity of the Zn–Ag catalyst, outperforming pure Ag and Au. Membrane electrode assemblies are constructed and coupled to a microbial process that converts the CO to acetate and ethanol. Combined, these concepts present pathways to design catalysts and systems for CO2 conversion toward sought‐after products. Abstract : Catalysts, electrodes, and membrane electrode assemblies (MEAs) are developed for the electrocatalytic conversion of CO2 ‐to‐CO and beyond. The system consists of highly porous Ag dispersed in a Zn matrix, which leads to high CO2 utilization as described by multiphysics modeling. Coupling to microbiology allows for further upgrading to multicarbon products.